A Better Integration of Industrial Robots in Romanian Enterprises and the Labour Market - Ivona Stoica (Răpan); Gheorghe Zaman; Marta-Christina Suciu; Victor-Lorin Purcărea; Cornelia-Rodica Jude; Andra-Victoria Radu; Aida Catană; Anamaria-Cătălina Radu (Applied Sciences, 2022)
The purpose of this paper is to illustrate the opportunities for adopting robotic applications, through a marketing mix perspective, as well as depicting the current state of industrial robot integration in Romanian enterprises and the labor market, in contrast to other economies of the European Union. In this research, we highlight the impact of industrial robots within enterprises, while also considering the perceived standard of living through GDP per capita. For this, we conducted exploratory research based on secondary data regarding the evolution of the robotics sector in Romania, in connection to the dynamics of the global and European Union robotics market. We also performed a principal components analysis, which revealed the main factors that contributed to the dynamics of nation-level enterprise statistics. Our analysis revealed that a higher integration of industrial robots contributed to the reduction of employment rates amongst all six EU countries considered, while also having positive correlations with the GDP per capita and apparent labor productivity. Mixed results were only observed for the impact of industrial robots on remuneration growth, suggesting the potential adverse effects automation could have on incomes.